GPS based tracking framework for walking pedestrian - Mantoro, Teddy; Ayu, Media Anugerah; Borovac, Amir (2011)
This paper discusses the problems in GPS based tracking system for walking pedestrian; these include the connectivity, map size and accuracy problems. These are the important factors affecting functionality of the GPS tracking system itself. The aim of this work is on how to setup an optimal connectivity, reducing map size of user location and to measure the acceptance of the location accuracy. To do this, a framework for tracking system using Global Positioning System (GPS) for positioning, General Packet Radio System (GPRS) and Short Message Service (SMS) for data transmission and Google Maps for displaying the location have been proposed. As a proof of concept, the prototype for the clients has been developed in various platforms including windows mobile (HTC), android (Samsung), iOS (iPhone) and Java Blackberry.